PENERAPAN WASIAT WAJIBAH BAGI AHLI WARIS NON MUSLIM (STUDI KASUS PERKARA NO.16K/AG/2010) - Kamaruddin, Kamaruddin (JURNAL ILMIAH MIZANI: Wacana Hukum, Ekonomi, dan Keagamaan, 2015)
Application of Obligatory Wills for the non-Muslim Heirs (Study Case No.16K/AG/2010).The basic consideration for the Supreme Court for giving the obligatory wills to the non-muslim heirsis based on case No. 16K / AG / 2010 are based on the principles of justice, where husband and wifehave long been fostering harmony and peace within a family; Relevance of obligatory wills against thecontemporary reality is very relevant for the creation of peace-oriented to the benefit, which meansthat the enforced of obligatory wills for the non-Muslim heirs will give a bit of space in the fulfillmentof their rights that are blocked according to Islamic law. This means that the discovery of the law byjudges more oriented to justice and legal values in society, so that the jurisprudence of the SupremeCourt to be a barometer on the court and appeal in the provision of obligatory wills for non-Muslimheirs. It is expected that the government to create legislation for obligatory wills more comprehensiveas necessary in answering the demands of the times, especially for non-Muslim heirs.